Analysis of the immunohistochemical and genetic expression pattern of kisspeptin in endometrial polyps - Paltacı, Şeyma İlayda; Günday, Özlem Kayacık; Erdoğan, Müjgan Özdemir; Fırat, Fatma; Yalçın, Gülsüm Şeyma; Akçalı, Nermin (Ceska gynekologie, 2024)
OBJECTIVE: Endometrial polyp (EP) is a type of pathology that is quite common in clinical practice. Although its exact etiology is not fully known, there is evidence to support that it is sensitive to hormonal stimuli. We aimed to investigate the relationship between kisspeptin (KP) and EP by comparing the genetic (tissue-blood) and immunohistochemical (IHC) expression of KP in EP lesions in patients with normal endometrial findings. MATERIALS AND METHODS: A prospective case-control study of 50 patients with EP (N = 25) and normal endometrial findings (N = 25) on biopsy and/or excision material was performed. Blood and biopsy samples obtained from all patients were stored at -80 °C. KP gene expression levels were determined from paraffin blocks, and peripheral venous blood samples obtained from biopsy specimens and IHC-H-score analysis were performed from paraffin blocks. EP and matched controls were compared for KP. RESULTS: After IHC, the KP H-score of the control group was higher than the EP group, and this difference was statistically significant; H-score: control: 5 (++; 1-15); polyp: 1 (+; 0-12) (P < 0.05). Although KP expression in both tissue and blood was higher in the control group than in the EP group, this difference was not statistically significant (P > 0.05). No significant correlation was found between IHC H-score and KP expression levels in tissue and blood. According to the ROC analysis, the tissue and blood KP expression cut-off value and area under the curve (AUC) predicting the likelihood of developing EP were not significant (tissue KP: 1.04, AUC: 0.570, P = 0.388, sensitivity 56%, specificity 60%, Blood KP: 1.06, AUC: 0.569, P = 0.401, sensitivity 80%, specificity 40%). CONCLUSIONS: Decreased KP expression level in EP lesions may predict the diagnosis of EP, and in the future, KP may have therapeutic potential for benign gynecological pathologies such as polyps.
Keywords: kisspeptiny; dospělí; Female; polypy; endometrial polyps; Adult; ženské pohlaví; kisspeptin; Uterine Diseases; endometrium; Immunohistochemistry; lidé; immunohistochemistry; studie případů a kontrol; imunohistochemie; prospektivní studie; Polyps; Case-Control Studies; Prospective Studies; reverse-transcription PCR (RT-PCR); Endometrium; nemoci dělohy; lidé středního věku; Middle Aged; Kisspeptins; Humans